Perancangan Aplikasi Point Of Sales (POS) Pada Minimarket Berkat Berbasis Web - Lase, Sandro David Julfirstson; Suharyanto, Cosmas Eko (JUTEKDISI, 2025)
As time goes by, the development of information technology has become increasingly modern, and has brought significant changes in various aspects of life, including in the world of business. One technological innovation that has been widely adopted is point of sales. The point of sales application is a system used to record sales transactions, manage inventory, and produce financial reports in real time. It is believed that the implementation of this application can increase operational efficiency, especially in retail businesses such as the Berkat Minimarket. The point of sales application design method at theThanks Minimarket is carried out using the DevOps method which is the most strategic project team method so that the application works in a structured manner, well integrated with the Firebase database. The Devops method consists of two parts, Development (plan, code, build, test) & Operation (deploy, operate, monitor, release). The web-based point of sales application at MinimarketThanks is also designed with modern technology and the application is always up to date (latest) to get an application system that works well. This system is equipped with role-based user authentication (admin and cashier) & is designed with a simple interface for user convenience. The results of this application design provide benefits, namely making it easier for admins to monitor stock and sales reports, as well as making it easier for cashiers to carry out transactions efficiently with the support of printing receipts.